The documentation and characterization of rock art in the Chiremba area of Epworth - Nyongoro, Revai (Midlands State University, 2017)
Rock art is one of the categories of the archaeological heritage which is found in various places locally, regionally and internationally. Rock paintings are non renewable resources which cannot be renewed once it has been destroyed. Chiremba Area is a segment of Epworth, a peri urban area which is located 13 kilometers to the South East of Harare. The place has got rock art sites in the Chiremba National Monument and outside the premises of the Monument. Previous researchers noted some of the rock art sites in the vicinity of the Chiremba Balancing Rocks. However little was done in relation to the documentation of the rock art sites. In addition rock art sites which are located close to the Muguta Secondary school were not identified or documented. Against this background, this stirred the researcher to have a conception about this study in relation to the identification, documentation, mapping, characterizing, and an attempt to interpret and to assess the conservation status of the rock art in the Chiremba area in Epworth. Rock art is one of the valuable cultural heritage assets for the nation which can play an instrumental role in eradicating poverty in the African societies through tourism industry and employing people who are jobless. In addition rock art can be used as a record of the prehistoric societies. Rock art paintings can also shed light about the socio-economic of the hunter gatherers and the agro pastoralist. However rock art need to be preserved, conserved and safe guarded jealously in order to prolong this form of valuable archaeological legacy which was left by the prehistorically societies .